Understanding Workaholism: Causes, Effects and Solutions - Belal Dahiam Saif Ghaleb (International Journal of Scientific Multidisciplinary Research, 2024)
Workaholism, often referred to as the compulsion to work excessively and uncontrollably, has garnered significant attention in organizational psychology. This paper aims to explore the multifaceted nature of workaholism, examining its causes, consequences, and potential interventions. Through a review of existing literature, this paper elucidates the psychological, social, and organizational factors contributing to workaholism and discusses its impact on individuals and organizations. Finally, strategies for managing and mitigating workaholism are proposed